OPTIMALISASI PENGELOLAAN INVENTARIS BENGKEL MELALUI IMPLEMENTASI SISTEM DIGITAL BERBASIS WEB DI SMK LEMURIA KUDUS - Bellachintya Reira Christata; Evanita (Jurnal Abdi Insani, 2026)
Digital transformation in the education sector has become a crucial factor in improving the efficiency of facilities and infrastructure management. This community service activity aims to optimize workshop inventory management at SMK Lemuria Kudus through the implementation of a web-based inventory system. Prior to the program, inventory management was conducted manually, resulting in unstructured data, difficulties in tracking equipment locations, and inefficiencies in borrowing and returning processes. The method used in this activity was a participatory problem-solving approach consisting of five stages: problem identification, system design and development, socialization, training, as well as evaluation and follow-up. The developed system includes features for equipment data management, stock quantity tracking, equipment location recording, and borrowing management. The results indicate improvements in efficiency, data accuracy, and ease of access to information. In addition, the partners were able to operate the system independently with a high level of understanding. Therefore, the implementation of a web-based digital system has proven to enhance the effectiveness of workshop inventory management and support the improvement of learning quality in vocational education.